2022
DOI: 10.1155/2022/9640574
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Dilemma and Solution of Copyright Justice System for Health Short Video under Network Big Data Environment Monitoring

Abstract: Short videos have quickly taken over the mobile screens of network users and established themselves as one of the most significant social platforms in the “Internet+era” as a new carrier of social culture. Short films have the qualities of high participation, strong engagement, high real-time, and quick propagation, which satisfy the needs of Internet users in interpersonal communication and reading or enjoyment in leisure time. This is against the backdrop of network big data environment monitoring. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…First, we only retrieved short-form videos published on the 3 most popular web-based video platforms in China, and therefore, we likely omitted eligible videos posted on other platforms. We deemed it unlikely that the inclusion of videos from other platforms would significantly affect our results since (1) other short-form video platforms have small numbers of registered users and rarely develop and publish original videos, instead reposting videos from the 3 platforms we included in this study [ 39 , 40 ], and (2) nearly all video developers, platform managers, and governmental department video supervisory officials are uneducated in the WHO injury prevention strategies, and thus, all videos posted on any web-based platform in China are likely to show similar patterns [ 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we only retrieved short-form videos published on the 3 most popular web-based video platforms in China, and therefore, we likely omitted eligible videos posted on other platforms. We deemed it unlikely that the inclusion of videos from other platforms would significantly affect our results since (1) other short-form video platforms have small numbers of registered users and rarely develop and publish original videos, instead reposting videos from the 3 platforms we included in this study [ 39 , 40 ], and (2) nearly all video developers, platform managers, and governmental department video supervisory officials are uneducated in the WHO injury prevention strategies, and thus, all videos posted on any web-based platform in China are likely to show similar patterns [ 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%